Nutritional aspects and yield of corn intercropped with cover crops and inoculated with diazotrophic bacteria - Nascimento, Vagner; Ferrari, Samuel; Lima, Ronaldo Cintra; Bonini, Carolina Dos Santos Batista; Prado, Evandro Pereira; Galindo, Fernando Shintate; Delfim, Jorge João; Arf, Orivaldo; Souza, Loiane Fernanda Romão de; Molina-Roco, Mauricio; Velázquez-Martí, Borja; Korany, Shereen Magdy; et al. (Frontiers in Sustainable Food Systems, 2025)
Intercropping corn with cover crops and inoculating with diazotrophic bacteria are sustainable low-cost practices that enhance nutrient cycling and uptake, leading to improved crop yield. Thus, this study evaluated the effects of monocropped corn versus intercropping with cover crops alongside foliar inoculation with Azospirillum brasilense. The experiment was conducted during the autumn-winter season in Dracena, within the Nova Alta Paulista region, Brazil, using a sandy-textured dystrophic Ultisol. The experiment was designed in a randomized blocks in a 4 × 2 factorial scheme, having four replicates. The treatments consisted of the cultivation of corn alone and intercropped with cover crops (Crotalaria spectabilis, Urochloa ruziziensis and C. spectabilis + U. ruziziensis) in the presence and absence inoculation with Azospirillum brasilense via foliar spray at crop growth stage V4. The inoculant contained strains AbV5 and AbV6 of A. brasilense (2 × 108 viable cells ml−1) applied at 500 ml ha−1. Intercropping corn with U. ruziziensis under inoculation, as well as corn with C. spectabilis + U. ruziziensis, regardless of inoculation, significantly increased grain yield in the second year. The corn intercropped with C. spectabilis irrespective of inoculation enhanced relative leaf chlorophyll content at the V4, V8, and R1 stages. In addition, intercropping corn with U. ruziziensis also enhanced leaf phosphorus (P) content while reducing sulfur (S) content. These findings suggest that farmers can optimize corn production by intercropping with Urochloa ruziziensis and Crotalaria spectabilis alongside diazotrophic bacterial inoculation to improve nutrient use efficiency and corn nutrition while reducing reliance on synthetic fertilizers and supporting low-carbon agriculture.